Leukotriene B4 loaded in microspheres regulate the expression of genes related to odontoblastic differentiation and biomineralization by dental pulp stem cells - Francine Lorencetti da Silva; Giuliana de Campos Chaves Lamarque; Fernanda Maria Machado Pereira Cabral de Oliveira; Paulo Nelson-Filho; Léa Assed Bezerra da Silva; Raquel Assed Bezerra Segato; Lúcia Helena Faccioli; Francisco Wanderley Garcia Paula-Silva (BMC, 2022)
Abstract Background Leukotriene B4 (LTB4) is a potent lipid mediator that stimulate the immune response. Because dental pulp inflammation and dentin repair are intrinsically related responses, the aim of this research was to investigate the potential of LTB4 in inducing differentiation of dental pulp stem cells. Methods Microspheres (MS) loaded with LTB4 were prepared using an oil emulsion solvent extraction evaporation process and sterility, characterization, efficiency of LTB4 encapsulation and in vitro LTB4 release assay were investigated. Mouse dental pulp stem cells (OD-21) were stimulated with soluble LTB4 or MS loaded with LTB4 (0.01 and 0.1 μM). Cytotoxicity and cell viability was determined by lactate dehydrogenase and methylthiazol tetrazolium assays. Gene expression were measured by quantitative reverse transcription polymerase chain reaction after 3, 6, 24, 48 and 72 h. Mineralized nodule formation was assessed after 28 days of OD-21 cell stimulation with LTB4 in mineralized media or not. Groups were compared using one-way ANOVA test followed by Dunnett's post-test (α = 0.05). Results Treatment with LTB4 or MS loaded with LTB4 (0.01 and 0.1 µm-μM) were not cytotoxic to OD-21 cells. Treatment with LTB4 modulated the expression of the Ibsp (integrin binding sialoprotein) and Runx2 (runt-related transcription factor 2) genes differently depending on the experimental period analyzed. Interestingly LTB4 loaded in microspheres (0.1 μM) allowed long term dental pulp cell differentiation and biomineralization. Conclusion LTB4, soluble or loaded in MS, were not cytotoxic and modulated the expression of the Ibsp and Runx2 genes in cultured OD-21 cells. When LTB4 was incorporated into MS, odontoblast differentiation and mineralization was induced in long term culture.